EFFECT OF VARIETY AND POULTRY MANURE LEVELS ON MOISTURE STRESS OF PAPAYA (Carica papaya) SEEDLINGS - Babagana, B. M.; Jibrin. A.D.; Fagam. A. S.; Shuaibu. Y.M. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
A field experiment to determine the effect of variety, moisture stress and poultry manure levels on the growth of papaya seedlings was conducted during the 2023 and 2024 dry seasons at Tafawa Balewa Road, Federal Low-cost Housing Estate Bauchi, Bauchi State, Nigeria. The treatments consisted of five Poultry manure levels (0.0kg, 0.2kg, 0.4kg, 0.6kg and 0.8kg) and two varieties of papaya seedlings (Calina IPB9 True Dwarf and Sun Grads). These were factorially combined and arranged in a randomized complete block design (RCBD) with three replications. The results revealed that, the treatment significantly (P≤0.05) affected plant height with poultry manure level (0.8kg) having a taller plants in 2023. However, in 2024 poultry manure level of 0.8kg/pot gave taller plants only at 8 and 10 weeks respectively. There was a significant (P≤0.05) effect on the number of leaves where poultry manure rate of 0.2kg gave a higher number in 2023, 0 and 0.2kg at 8 weeks and 0.8kg at 12 weeks in 2024. A significant (P≤0.05) effect of the treatments was recorded on stem girth at 8 and 10 weeks with poultry manure level of 0.8kg having bigger stem girth at 2023. Poultry manure levels of 0.2kg at 12 weeks in 2023 and 0.6kg/pot at 4 weeks recorded statistically (P≤0.05) higher node numbers. Furthermore, there was a significant (P≤0.05) effect in moisture stress where poultry manure level of 0.2kg showed higher remaining leaves (RML), taller plants (0.6kg), bigger stem girth (0.6kg and 0.8kg), and higher dry matter weight (0.2kg) in 2023. In 2024, 0.6kg poultry manure level records higher nodes (P≤0.05) with no significant difference in the remaining measured parameters. The application of cured poultry manure at 0.2kg, 0.6kg and 0.8kg levels enhanced growth performance and resistance to moisture stress of the papaya seedlings. Trials with other organic manure as a source of nutrients are therefore recommended.